Thermoacoustic range verification during pencil beam delivery of a clinical plan to an abdominal imaging phantom. (June 2021) - Patch, Sarah K.; Nguyen, Chinh; Dominguez-Ramirez, Diego; Labarbe, Rudi; Janssens, Guillaume; Cammarano, Diego; Lister, Jake; Finch, Christopher; Lambert, Jamil; Pandey, Jeevan; Bennett, Christopher; Porteous, Elizabeth; et al.
Highlights: Fast (4-6 us) and stress-confined, delivery enables thermoacoustic range verification. Submillimeter range accuracy was achieved for beamlets that delivered ~0.5 Gy to soft tissue. Estimates are accurate relative to ultrasound images soundspeed inhomogeneity Synchrocyclotrons deliver stress-confined proton pulses. Acoustic ringing indicated beam traversed bone; metallic implants will also cause ringing. Abstract: Purpose: The purpose of this phantom study is to demonstrate that thermoacoustic range verification could be performed clinically. Thermoacoustic emissions generated in an anatomical multimodality imaging phantom during delivery of a clinical plan are compared to simulated emissions to estimate range shifts compared to the treatment plan. Methods: A single-field 12-layer proton pencil beam scanning (PBS) treatment plan created in Pinnacle prescribing 6 Gy/fraction was delivered by a superconducting synchrocyclotron to a triple modality (CT, MRI, and US) abdominal imaging phantom. Data was acquired by four acoustic receivers rigidly affixed to a linear ultrasound array. Receivers 1–2 were located distal to the treatment volume, whereas 3–4 were lateral. Receivers' room coordinates were computed relative to the ultrasound image plane after co-registration to the planning CT volume. For each prescribed beamlet, a set of thermoacoustic emissions corresponding to varied beam energies were computed. Simulated emissions were compared to measured emissions to estimate shifts of the Bragg peak. Results: Shifts were small for high-dose beamlets that stopped in soft tissue. Signals acquired by channels 1–2 yielded shifts of - 0.2 ± 0.7 m m relative to Monte Carlo simulations for high dose spots (~40 cGy) in the second layer. Additionally, for beam energy ≥ 125 MeV, thermoacoustic emissions qualitatively tracked lateral motion of pristine beams in a layered gelatin phantom, and time shifts induced by changing phantom layers were self-consistent within nanoseconds. Conclusions: Acoustic receivers tuned to spectra of thermoacoustic emissions may enable range verification during proton therapy.